Development and Evaluation of Communicative English Competency Program for First Year University Students - Arriane Kris Manalastas (SEAMEO QITEP in Language, 2025)
This research addresses the development, implementation, and evaluation of an English Proficiency Program that is tailored for first year university students. During the implementation phase, a positive shift in competency test scores is observed (pre-test mean of 92.00 to post-test mean of 102.40), indicating overall improvement. The significant difference between pre- and post-test scores (p-value= 0.00) underscores the program's positive impact on general competency. The perceived effectiveness, with a grand mean of 4.64, attests to the program's efficacy in enhancing various language proficiency aspects. Participants express consensus that the program is well-executed, meeting its objectives, and significantly contributing to improved English language proficiency. It is therefore recommended that educators should address language deficiencies through targeted interventions particularly in grammar and writing competencies of students, incorporate technology, implement long-term impact assessments, extend program duration, and integrate successful elements into broader educational activities. These recommendations collectively form a comprehensive and effective approach for enhancing English language proficiency among students.